Investigating Register of Conversational Ticketing Company between Salespersons and Costumers - Gino Ali; Vina Fathira (Enlighted Journal, 2023)
Language registers are significant because they offer several options for language and subject conditioning. This study aimed to explain the use of formal and informal registers used by salesmen and customers in the Muhibbah Tour and Travel Company found in their interaction through WhatsApp. The research method used in this thesis research was a qualitative. The data was collected by taking screenshots of the WhatsApp chats between the salesmen and the customers. The results of this study indicated that there were 59 chats by salesmen and 73 chats by customers. From these results it was found that the use of formal registers referred to several categories, namely: passive voice (salesmen 10%, customers 8%), no abbreviation (salesmen 13%, customers 19%), politeness words (salesmen 20%, customers 15%), facts or references (salesmen 15%, customers 0%), and technical / business vocabularies (salesmen 8%, customers 5%). Meanwhile, the use of informal registers also referred to several categories, including: active voice (salesmen 10%, customers 16%), abbreviation (salesmen 33%, customers 34%), rapport or familiarity speech (salesmen 6%, customers 13%), and expressing opinions (salesmen 6%, customers 6%). For the context of the situation of using registers, the researcher found: field (asking and giving information, ordering, and getting confirmation), tenor (social status, relative status, and social distance), and mode (written mode). The use of formal and informal registers on WhatsApp chats between marketing employees of the Muhibbah Tour and Travel Company was quite balanced, where the chats seemed neither rude nor stiff.